The integration of color cluster and distribution for image retrieval - Wang, Yin Chung (Faculty of Computer Science and Information Technology, 2000)
Images are generated in many application areas such as image processing, multimedia, digital libraries, remote sensing, astronomy, database application and other related area at fast rate. A content-based image retrieval (CBIR) systems needs to provides an effective and efficient to image databases, based on visual content which includes colour, shape, texture and spatial features.